Developing timely insights into Pseudomonas aeruginosa quorum sensing therapeutics through text mining - Jorge, Paula Alexandra Silva (2016)
Publicado em "Biofilms7: microbial works of art: book of abstracts". ISBN 978-989-97478-7-6